The methods of defining terms found in theses of the EFL students - Rahmadi Nirwanto (Journal on English as a Foreign Language, 2015)
The study is intended to describe the methods of defining terms found in the theses of the English Foreign Language (EFL) students of IAIN Palangka Raya. The method to be used is a mixed method, qualitative and quantitative. Quantitative approach was used to identify, describe the frequencies, and classify the methods of defining terms. In interpreting and explaining the types of method to be used, the writer used qualitative approach. In qualitative approach, data were described in the form of words and explanation. The findings show that there were two methods of defining terms, dictionary approach and athoritative reference.